Anti-melanogenic and anti-oxidant activities of ethanol extract of Kummerowia striata: Kummerowia striata regulate anti-melanogenic activity through down-regulation of TRP-1, TRP-2 and MITF expression. (2019) - Lee, Jae Yeon; Cho, Young-Rak; Park, Ju Hyoung; Ahn, Eun-Kyung; Jeong, Wonsik; Shin, Hyoung Seok; Kim, Mi-Sun; Yang, Seung Hwan; Oh, Joa Sub
Highlights: Ethanol extract of Kummerowia striata is a potent antioxidant. It inhibits melanin synthesis by downregulating tyrosinase and related proteins. It may be used in cosmetics for skin whitening and reducing wrinkles. Abstract: Kummerowia striata ( K. striata ) is used as a traditional medicine for inflammation-related therapy. To determine whether it has beneficial anti-melanogenic and anti-oxidant activities, we investigated the biological activities of the ethanol extract of Kummerowia striata (EKS) using a variety of in vitro and cell culture model systems. The anti-melanogenic activity was assessed in B16F10 melanoma cells in terms of melanin synthesis and in vitro tyrosinase inhibitory activity. The anti-oxidant assays were performed using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2ʹ-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS). EKS showed strong anti-oxidant activities in DPPH and ABTS assays. The mRNA transcription levels and protein expression levels of tyrosinase, tyrosinase-related protein 1, tyrosinase-related protein 2, and microphthalmia-associated transcription factor decreased in a dose-dependent manner with EKS treatment. Additionally, EKS did not affect cell viability at different concentrations used in this study, indicating that the mechanism of action of EKS-mediated inhibition of melanin synthesis does not involve cytotoxicity. Also, we confirmed that p-coumaric acid and quercetin are important compounds for anti-melanogenesis and antioxidant properties of EKS. Collectively, our findings demonstrate for the first time that EKS possesses anti-melanogenic and anti-oxidant activities. Further evaluation and development of EKS as a functional supplement or cosmetic may be useful for skin whitening and reducing wrinkles.